2011
DOI: 10.1111/j.1095-8312.2011.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator sharing in dioecious figs (Ficus: Moraceae)

Abstract: As one of the most specialized pollination syndromes, the fig (Ficus)-fig wasp (Agaonidae) mutualism can shed light on how pollinator behaviour and specificity affect plant diversification through processes such as reproductive isolation and hybridization. Pollinator sharing among species has important implications for Ficus species delimitation and the evolutionary history of the mutualism. Although agaonid wasp pollinators are known to visit more than one host species in monoecious figs, pollinator sharing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 55 publications
3
63
2
2
Order By: Relevance
“…Previous studies have reported a significant amount of pollinator sharing in monoecious figs [13,17,19,29], while pollinator sharing in dioecious figs was predicted to be rather low [19,28] [19], only this study experimentally compared the ratio of taxa within same section and that from different sections. The pollinator sharing ratio may be overestimated with wasps collected from receptive syconia if wasps have lower survival on 'non-typical' hosts, compared with the ratio calculated based on wasps emerging from syconia in the male flower phase [14].…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported a significant amount of pollinator sharing in monoecious figs [13,17,19,29], while pollinator sharing in dioecious figs was predicted to be rather low [19,28] [19], only this study experimentally compared the ratio of taxa within same section and that from different sections. The pollinator sharing ratio may be overestimated with wasps collected from receptive syconia if wasps have lower survival on 'non-typical' hosts, compared with the ratio calculated based on wasps emerging from syconia in the male flower phase [14].…”
Section: Discussionmentioning
confidence: 90%
“…Once emerged, we collected ten female and ten male pollinating wasps for storage in 100% ethanol. A second collection of five males and five females was done using tubes filled with colour changing silica gel topped with cotton wool as per (Moe et al, ). For each tree, we used a single female fig‐wasp from the silica gel collections for DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, coexistence of distantly related pollinators has been documented [14]. Genetic data on other species suggest that, while more than one wasp species may occur across the fig-distribution range, a single pollinator species is usually present locally [11,15,16]. In some cases, the two wasp species pollinating the same Ficus species are associated with different environments [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous observations of agaonid wasps associated with a Ficus species that sometimes also visit (and pollinate) another Ficus species [16]. The importance of such events in terms of the potential for genetic introgression among Ficus species should not be understated [7].…”
Section: Introductionmentioning
confidence: 99%